Marine Protected Areas: Spanish context and the case of “Os Miñarzos” - Burgos, Andrés (2014)
The analysis of the fisheries status in the world suggests that the state of the main marine resources is worrying, and that the fishery sector has been under unsustainable conditions. Over the last decades, the Marine Protected Areas have been established as global planning tools to compensate for the effects of overfishing, and ensure thesustainability of biological productivity and human uses. However, many of them are limited to the simple name, without detailed knowledge of the ecosystems that host, neither to include effectively local communities in their implementation and management, key requirements to manage these areas in a holistic and integral way.This paper addresses the marine protected areas as tools of governance based in the fisheries co-management that can promote the conservation of biodiversity and ecosystem services, as well as the promotion of human welfare. For that, we describe the history of the "Os Miñarzos” Marine Reserve of Fishing Interest (Galicia / Spain),covering its six years of life. It is hoped that this paper will help to disseminate this initiative promoted by the local fisheries, and that it can contribute to the discussion on the role of marine protected areas in protecting the long-term ecological integrity and sustainable use of natural ecosystems.